Parents’ perspective in the evaluation of a parental report inventory for the assessment of child communication development - Anđelković Darinka; Savić Maja; Tutnjević Slavica (Zbornik Instituta za pedagoška istraživanja, 2023)
Parents’ reports are accepted in practice and can be a valid and reliable source of information in research on children’s communicative development and any delays in this. Nevertheless, parents’ reports may have important limitations that need to be considered: parental positive bias; parents’ understanding of the child language comprehension; and parents’ education and limited linguistic knowledge. In this paper, we take the stance that parents are most interested in an adequate assessment, and obtaining reliable input from them is certainly important. We amplify the voice of parents by synthesizing their experiences with a parental report inventory as a method based on the usage of the adapted version of the MacArthur-Bates Communicative Development Inventory. With that aim, we conducted a qualitative inductive thematic analysis of focus group discussions and additional open-ended validation questions. Six emerging themes and sub-themes were identified and presented with illustrative quotations. Results revealed that the adaptation of original CDIs to languages with radically different morpho-syntactic structures may produce items that are hard to recognize and understand without a context. We bring to light parent-specific difficulties in performing this task and provide a critical understanding of parents’ reports as a method of language development assessment. We discuss potential solutions to parents’ dilemmas that inevitably arise when reporting on their child’s communication, as well as answers to researchers’/practitioners’ dilemmas regarding the validity and reliability of parental reporting.